Strength assessment of rice hills from different planting distance by loading simulation - Edi Santosa; Herdhata Agusta; Dwi Guntoro; Sofyan Zaman (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2020)
Plant spacing arrangement might benefit hill strength from the impact of strong wind velocity during extreme weather situations. Here, a loading test to evaluate rice hill strength was performed on Ciherang variety grown in square and double row spacing 2:1. The research was conducted at Cilubang village, Dramaga, Bogor, West Java, Indonesia from March to May 2017. Weight holding capacity was evaluated in 85 days after transplanting on four levels of hill height, i.e., 80 cm, 60 cm, 40 cm, and 20 cm above soil level with three-time replication. The results showed that double-spaced hills had 66.0 % ± 3.1 % stronger than those of square spacing at all height measurement. To lodge a hill into 20 cm to 40 cm from soil level, it required 346.7 g to 741.7 g in square spacing, and 555.2 g to 1149.2 g in double row spacing. Stronger hills in double row spacing seemed to correlate with a higher number of tiller and hills architecture; it requires further study in the role of both factors on the hill strength improvement. The present study recommends applying double row spacing to improve rice hill strength especially at a time with a high chance of lodging by strong wind incident.